A Case of Type 1 Triallelic Patterns at D5S818, D18S51, D6S1043, and FGA Demonstrated by Short Tandem Repeat Analysis. (25th April 2022) - Fan, Jing; Zhang, Ai-Ping; Zheng, Zhong-Zheng; An, Lin; Xiao, Pei-Li; Li, Dai-Yang; Du, Ke-Ming; Xiong, Hao
Abstract : The triallelic pattern of short tandem repeat (STR) is rare; especially, the case where this pattern exists at 4 loci has not been reported. Here, we report the type 1 triallelic patterns at D5S818, D18S51, D6S1043, and FGA from a Chinese family, which were observed during our routine chimerism assays. Before hematopoietic stem cell transplantation, the blood sample of the certain patient was analyzed by performing chimerism analysis. A preliminary STR analysis was also performed on the samples of the patient's parents. STR signal data illustrated that the sum of the peak chart areas of the two types inherited from the father was basically the same as that of the mother, belonging to the type 1 triallelic pattern. In addition, the patient's elder sister's STR result appeared to be normal. Altogether, we presented a pedigree, in which the triallelic pattern was linked by inheritance in the family. This is the first reported case of the triallelic pattern at D5S818, D18S51, D6S1043, and FGA all around the world. We hope that in the future there will be any tools to achieve accurate verification against this possibility.